Integrated health and care systems in England: can they help prevent disease?. Issue 1 (26th February 2020) - Briggs, Adam D M; Göpfert, Anya; Thorlby, Ruth; Allwood, Dominique; Alderwick, Hugh
Abstract : Objectives: Over the past 12 months, there has been increasing policy rhetoric regarding the role of the National Health Service (NHS) in preventing disease and improving population health. In particular, the NHS Long Term Plan sees integrated care systems (ICSs) and sustainability and transformation partnerships (STPs) as routes to improving disease prevention. Here, we place current NHS England integrated care plans in their historical context and review evidence on the relationship between integrated care and prevention. We ask how the NHS Long Term Plan may help prevent disease and explore the role of the 2019 ICS and STP plans in delivering this change. Methods: We reviewed the evidence underlying the relationship between integrated care and disease prevention, and analysed 2016 STP plans for content relating to disease prevention and population health. Results: The evidence of more integrated care leading to better disease prevention is weak. Although nearly all 2016 STP plans included a prevention or population health strategy, fewer than half specified how they will work with local government public health teams, and there was incomplete coverage across plans about how they would meet NHS England prevention priorities. Plans broadly focused on individual-level approaches to disease prevention, with few describing interventions addressing social determinants of health. Conclusions: For ICSs and STPs to meaningfully prevent disease and improve population health, they need to look beyond their 2016 plans and fill the gaps in the Long Term Plan on social determinants.